Esteganografia do ponto de vista da Teoria dos códigos - Campos, Alexandre Henrique Afonso (2014)
Steganography is a subject that became very important in the study of information security. When it was related to Coding Theory, which was well developed, the research on this matter rapidly increased. In this work, we will introduce Steganography and we will show how the Coding Theory an help in its study; perfect codes will be related to a kind of stegoscheme and we will see the effect of wet paper codes in Steganography.